2013
DOI: 10.2134/agronj2013.0084
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Irrigation Levels Affect Boll Distribution, Yield, and Fiber Micronaire in Cotton

Abstract: or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. U pland cotton is a crop with an indeterminate fruiting habit that is influenced by the environment in which the plant grows. Effective flowering (flowering on fruiting sites that contribute to economic yield) begins about 60 d after the crop is planted and continues for about 4 to 6 wk (Bruns, 2009), depending on cultivar and environmental conditions. Flower prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 22 publications
6
52
0
Order By: Relevance
“…Several studies have been conducted, showing that prolonged water deficit during the cotton cultivation cycle affects growth, productivity, and quality of the fibers (SNOWDEN et al, 2013;ZONTA et al, 2015a, ZONTA et al, 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted, showing that prolonged water deficit during the cotton cultivation cycle affects growth, productivity, and quality of the fibers (SNOWDEN et al, 2013;ZONTA et al, 2015a, ZONTA et al, 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of vertical and horizontal flowering intervals for this study suggested that, even though flowering intervals are decreased, the two-node delay from first to second sympodial position was still a general pattern among all cultivars (Fig. It has been shown that the fraction of first-position fruit depends on cultivar, planting density, irrigation, fertility, insect pressure, and other influences (Kerby et al, 1986;Reddy et al, 1992;Pettigrew, 2004;Siebert and Stewart, 2006;Snowden et al, 2013). It has been shown that the fraction of first-position fruit depends on cultivar, planting density, irrigation, fertility, insect pressure, and other influences (Kerby et al, 1986;Reddy et al, 1992;Pettigrew, 2004;Siebert and Stewart, 2006;Snowden et al, 2013).…”
Section: Flowering and Maturitymentioning
confidence: 66%
“…Many cotton irrigation studies have recognized the impacts of water deficit on cotton growth, yield, and fiber quality (Dağdelen et al, 2009;DeTar, 2008;Gerik et al, 1996;Howell et al, 2004;Peng et al, 1989;Pettigrew, 2004), and a considerable amount of research has been conducted on the effects of severe, moderate, and low water stress on cotton boll distribution and mass (Ritchie et al, 2009;Snowden et al, 2013;Yang and Zhou, 2010), but it is relatively unknown if equal or more efficient boll production results could be achieved with less irrigation applied at precise intervals. Another limitation of existing work is that there is not a defined response to the interaction between various periods of water stress on cotton production.…”
Section: Irrigation Timing and Rate Affect Cotton Boll Distribution Amentioning
confidence: 99%
“…Reduced levels of irrigation early in the growing season may have fewer adverse effects than during flowering (Snowden et al, 2013). However, previous work has focused on an all-ornothing approach during periods of water deficit stress.…”
Section: Irrigation Timing and Rate Affect Cotton Boll Distribution Amentioning
confidence: 99%